Influence of Physical Factors and Various Complex Media on Growth and Bacteriocin Production of Two-synergistic Peptide with Heat Stable Bacteriocin Producer, Enterococcus faecium NKR-5-3, Isolated from Thai Fermented Fish - Pongtep Wilaipun; Takeshi Zendo; Mathana Sangjindavong; Sunee Nitisinprasert; Vichien Leelawatcharamas; Jiro Nakayama; Kenji Sonomoto (Agriculture and Natural Resources, 2002)
Enterococcus faecium NKR-5-3, isolated from Thai fermented fish (Pla-ra), produced an interested two-synergistic peptide bacteriocin with heat stable and broad spectrum activity. The influence of complex media and culture condition on growth as well as bacteriocin production of E. faecium NKR-5-3 has been studied. From 8 indicator strains used, Enterococcus faecalis ATCC 19433 was found to be the most sensitive strain. The bacteriocin to be diluted with distilled water containing 0.1% (v/v) Tween 80 increased 2-fold to 4-fold of its activity against indicator strains when compared with distilled water. In M-MRS broth, bacteriocin production reached maximum level at 30°C and decreased with the increasing of culture temperature. Among different 6 complex media for lactic acid bacteria cultured at 30°C, M 17 broth with the initial pH of 7.5 yielded the maximum growth and bacteriocin production of E. faecium NKR-5-3. Growth and bacteriocin production decreased when it was cultured in M 17 broth containing more than 1% NaCl and they were completely inhibited in M 17 broth containing more than 9% NaCl. Bacteriocin activity reached a detectable level at the early exponential phase and increased due to the cell growth to the maximum level at the end of exponential phase in 22 hr of incubation, which displayed a primary metabolite production.